A novel EHD1/CD44/Hippo/SP1 positive feedback loop potentiates stemness and metastasis in lung adenocarcinoma. Issue 4 (29th April 2022) - Liu, Yuechao; Song, Yang; Cao, Mengru; Fan, Weina; Cui, Yaowen; Cui, Yimeng; Zhan, Yuning; Gu, Ruixue; Tian, Fanglin; Zhang, Shuai; Cai, Li; Xing, Ying
Abstract: Background: There is growing evidence that endocytosis plays a pivotal role in cancer metastasis. In this study, we first identified endocytic and metastasis‐associated genes (EMGs) and then investigated the biological functions and mechanisms of EMGs. Methods: Cancer stem cells (CSCs)‐like characteristics were evaluated by tumour limiting dilution assays, three‐dimensional (3D) spheroid cancer models. Microarray analysis was used to identify the pathways significantly regulated by mammalian Eps15 homology domain protein 1 (EHD1) knockdown. Mass spectrometry (MS) was performed to identify EHD1‐interacting proteins. The function of EHD1 as a regulator of cluster of differentiation 44 (CD44) endocytic recycling and lysosomal degradation was determined by CD44 biotinylation and recycling assays. Results: EHD1 was identified as a significant EMG. Knockdown of EHD1 suppressed CSCs‐like characteristics, epithelial–mesenchymal transition (EMT), migration and invasion of lung adenocarcinoma (LUAD) cells by increasing Hippo kinase cascade activation. Conversely, EHD1 overexpression inhibited the Hippo pathway to promote cancer stemness and metastasis. Notably, utilising MS analysis, the CD44 protein was identified as a potential binding partner of EHD1. Furthermore, EHD1 enhanced CD44 recycling and stability. Indeed, silencing of CD44 or disruption of the EHD1/CD44 interaction enhanced Hippo pathway activity and reduced CSCs‐like traits, EMT and metastasis. Interestingly, specificity protein 1 (SP1), a known downstream target gene of the Hippo‐TEA‐domain family members 1 (TEAD1) pathway, was found to directly bind to the EHD1 promoter region and induce its expression. Among clinical specimens, the EHD1 expression level in LUAD tissues of metastatic patients was higher than that of non‐metastatic patients. Conclusions: Our findings emphasise that EHD1 might be a potent anti‐metastatic target and present a novel regulatory mechanism by which the EHD1/CD44/Hippo/SP1 positive feedback circuit plays pivotal roles in coupling modules of CSCs‐like properties and EMT in LUAD. Targeting this loop may serve as a remedy for patients with advanced metastatic LUAD. Abstract : EHD1 interacts with the CD44‐ICD, promoting CD44 recycling and upregulating CD44 expression. CD44 upregulation inhibits Hippo signalling activity, activating expression of downstream target genes involved in stemness and EMT. SP1, as a downstream target of Hippo signalling, in turn transcriptionally activates EHD1 expression, finally forming an EHD1/CD44/Hippo/SP1 positive feedback loop that drives LUAD metastasis.